Innovative Cast Glass Surfaces for Improved Photovoltaic Efficiency in BIPV Systems - McGuire, Peter James (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2026)
Abstract This thesis investigates the current state of the Building Integrated Photovoltaics (BIPV) industry and identifies an area of potential product design for vertical facades, using cast glass textures over standard photovoltaic solar panels to maximise light capture efficiency and to improve on the visual aesthetic of the solar panels. To simulate the angle of the Earth to Sun, this research involves the production and testing of a selection of sample cast glass profiles using solar simulator in laboratory to record the light capture and energy generation. Each sample is made in the kiln using heat and gravity to mould the glass in to lens shapes and other textures for testing. In order to visually assess the difference between standard photovoltaic solar panels and the cast glass product, an experimental test station is to be set up to view the idea on full scale proportion. The market for BIPV glass products at present shows many glass products using opaque inks or laminated interlayers to offer a coloured solution to the flat monotone black standard solar panel. These products lose a considerable amount of energy by blocking the light. The glass panels developed in this research (to be called PVGlass) are made by using low iron Opti clear glass with the design on the surface to remain clear to maximise light and to redirect light from changing angles on to the solar cells. This is the principle of the Fresnel lens used in lighthouses to maximise the light outwards for navigation. PVGlass work in the reverse; the light is captured from the sun and directed inward on the vertical building façade to create energy for the building. The texture of the cast glass surface becomes the visual difference and by using clear glass the obstruction of natural light is minimised. For aesthetic improvement, the light is broken on the surface giving a visually dynamic moving surface that disguises the monotone dark solar panel while achieving 95 % of efficiency of standard solar panel.
APPROVED